[Am Jungstädtischen Holzraum aut. odb. Karol Nowaliński]. - Nowaliński, Karol (1935- ). (odb. Karol Nowaliński], 1986)
Przedstawia na pierwszym planie Kanał Heckergraben, w głębi wylot ul. Am Holzraum, 20.06.1928 r.